(untitled) (Journal of Science and Technology, 2022)
Mining companies usually face challenges of chronic clogging of screening media which causes frequent downtime, low efficiency and wear. Investigation of weight clogged (the amount of ma-terial retained on the sieve after screening) in the vibrating screen was carried out on sulphide ore samples during mining operations to study the effects of amplitude of vibration, aperture size and quantity of feed on weight clogged in the vibrating screen and to optimize the weight clogged during mining operations. Sieving analysis experiment was performed on the samples with a vibrator using the 23 design of experiments (DOE) method. The results showed that the aperture size was the most influencing factor of weight clogged, followed by the quantity offeed. Amplitude posed the least influence on weight clogged. The effects can be optimized at high am-plitude (3 cm), at high aperture size (150 mm) and at low quantity offeed (600 g).